Long Non-coding RNA H19 Suppression Protects the Endothelium Against Hyperglycemic-Induced Inflammation via Inhibiting Expression of miR-29b Target Gene Vascular Endothelial Growth Factor a Through Activation of the Protein Kinase B/Endothelial Nitric Oxide Synthase Pathway - Cheng, Xiao-wen; Chen, Zhen-fei; Wan, Yu-feng; Zhou, Qing; Wang, Hua; Zhu, Hua-qing (Frontiers in Cell and Developmental Biology, 2019)
It has been shown that non-coding RNAs (ncRNAs) play an important regulatory role in pathophysiological processes involving inflammation. Gene vascular endothelial growth factor A (VEGFA) also participates in the inflammatory process. However, the relationships between ncRNAs and VEGFA are currently unclear. Here, this study was designed to determine the relationship between long non-coding RNA (lncRNA) H19, mircoRNA29b (miR-29b) and VEGFA in the development of diabetes mellitus (DM). We demonstrated that H19 is upregulated and miR-29b downregulated in individuals with diabetes. H19 binds miR-29b directly. VEGFA is the target of miR-29b in the vascular endothelium of individuals with diabetes. We found that positive modulation of miR29b and inhibition of H19 and VEGFA significantly attenuates high glucose-induced endothelial inflammation and oxidative stress and that the protein kinase B/endothelial nitric oxide synthase (AKT/eNOS) signal pathway in endothelial cells is activated through regulation of the above endogenous RNAs. On the basis of these results, we conclude that H19 suppression protects the endothelium against high glucose-induced inflammation and oxidative stress in endothelial cells by upregulation of miR-29b and downregulation of VEGFA via activating the AKT/eNOS signal pathway. Overall, these results suggest a novel link between dysregulated ncRNA expression, inflammation, and the signaling pathway in the vascular endothelium of individuals with diabetes, indicating a promising strategy for preventing cardiovascular disease in such individuals.